2002
DOI: 10.1002/jcb.10192
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X receptors and retinoid response in neuroblastoma cells

Abstract: Retinoic acid (RA) modulates differentiation and apoptosis of neural cells via RA receptors (RARs) and retinoid X receptors (RXRs). Neuroblastoma cells are potentially useful models for elucidating the molecular mechanisms of RA in neural cells, and responses to different isomers of RA have been interpreted in terms of differential homo- and heterodimerization of RXRs. The aim of this study was to identify the RXR types expressed in neuroblast and substrate-adherent neuroblastoma cells, and to study the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
0
18
1
Order By: Relevance
“…In order to investigate the most likely mode of action of retinoic acid/RXR at the subcellular level, gene expression studies were performed using the northern blot technique. It was found that retinoic acid causes a strong upregulation of the expression of the RXR gene, a finding that is in accordance with the related receptors present in triploblasts; in these animals a tissue-and stage-dependent expression of RXRs is known (see Rana et al, 2002). Since this effect is observed in S. domuncula with all-trans retinoic acid we assume that the morphogen is isomerized in the animal to 9-cis-retinoic acid, the characteristic ligand for RXRs.…”
Section: Discussionmentioning
confidence: 55%
“…In order to investigate the most likely mode of action of retinoic acid/RXR at the subcellular level, gene expression studies were performed using the northern blot technique. It was found that retinoic acid causes a strong upregulation of the expression of the RXR gene, a finding that is in accordance with the related receptors present in triploblasts; in these animals a tissue-and stage-dependent expression of RXRs is known (see Rana et al, 2002). Since this effect is observed in S. domuncula with all-trans retinoic acid we assume that the morphogen is isomerized in the animal to 9-cis-retinoic acid, the characteristic ligand for RXRs.…”
Section: Discussionmentioning
confidence: 55%
“…6 All-trans retinoic acid (ATRA) has been used as a chemotherapeutic agent with some success, 7 although 13-cis-retinoic acid (13-cis-RA) is preferred due to its more favorable pharmacokinetics. [8][9][10] Indeed, a phase I trial showed that higher and more sustained drug levels are obtained through microarray analyses, we identified the Mpped2 gene as differentially expressed in two neuroblastoma cell lines induced to differentiation with all-trans retinoic acid. Mpped2 codes for a new metallophosphodiesterase protein, the expression of which inhibits cell proliferation and soft agar colony formation in sh-sY5Y cells.…”
Section: Introductionmentioning
confidence: 99%
“…Gel shift assays suggest that heterodimers of RARg and RXRb predominate in the neuroblastoma cell model used for our fenretinide studies. 7 Since retinoic acid induces differentiation of neuroblastoma cells, 8 fenretinide-induced death of these cells may result from activation of RARg in combination with fenretinidegenerated free radicals or oxidative stress. This hypothesis leads to two predictions: (1) increased expression of RARg should increase cell death in response to fenretinide, and (2) increased levels of RARg would not affect cell death in response to retinoic acid since retinoic acid isomers induce differentiation without increasing oxidative stress.…”
mentioning
confidence: 99%
“…14 In contrast to recent results for squamous carcinoma cells, 15 RARg overexpression did not significantly affect fenretinide-induced apoptosis, and this suggests that RARg activation by fenretinide does not have a major role in apoptosis of neuroblastoma cells. One possibility is that, despite its minor contribution to RAR-RXR heterodimers in these cells, 7 RARb may be involved in apoptosis. Alternatively, the ability of RARb/g (but not RARa 6 ) antagonists to block fenretinide-induced apoptosis may not be mediated directly by RARs.…”
mentioning
confidence: 99%